Chapter Introduction. An Archaeology of Modernism - Méndez Baiges, María Teresa (Studi e saggi, 2022)
The book meticulously analyses the history of the critical reception of avantguard art through the interpretations received by one of its greatest emblems, Les Demoiselles d'Avignon by Picasso, 1907. Since Les Demoiselles has been considered over this century the true paradigm of Modern Art, this book is, fundamentally, a sort of synthesis of the discourses about Modernism from formalism, iconology, Leo Steinberg's 'Other Criteria', sociological, the biographical and psychoanalytical theses, cultural and historicist and lastly, the impact of post-structuralism and the feminist, post-colonialist and transnational interpretations. The final chapter deals with the artistic versions of Les Demoiselles d'Avignon made by artists. It is an essay on the different versions and identities of Modern Art and Modernism that have been produced throughout the last century.